Identification technologies evaluation method: an application in cattle chain - Cabral Ribeiro, Priscilla Cristina; Batalha, Mário Otávio; M. Chudoba, Katherine; Bailey, Deevon; Scavarda, Annibal Jose (Brazilian Journal of Operations & Production Management, 2018)
The objective of this paper is to apply an identification technologies evaluation method in cattle chain in a sample in Brazil and in USA. These technologies are information and communication technologies, such as Radio Frequency Identification and barcode. The research methodology used was a qualitative study, with an extensive literature review on information technology, information systems, and Radiofrequency evaluation methods. A scale was created to decide what decision the case study has to take according to its technology. The method proposed can contribute to the theory of information technology evaluation and can offer practitioners an efficient and effective way to evaluate prospective information technology implementations. The rankings showed that American respondents evaluate RFID with a better performance in security variables. Brazilian agents evaluate Radiofrequency with a better performance in technical and organizational variable. The scale revealed that the Americans have more agents in Group B (8), which means reevaluation of the identification method, and just one in Group A, meaning that it has to change its information technology. Brazilian agents have more cases in Group B (6), than group C (3), and Group A (1). This means that the majority of the sample has to reevaluate their method to trace cattle.